Is care in conjunction with consultation liaison psychiatry better than standard care for adults with mental health disorders seen in a primary care setting?. Issue 10 (October 2017) - Bernhardt, Jeremia; Gilles, Ryan
Abstract : EVIDENCE‐BASED ANSWER : Treating mental health disorders in a primary care setting using a consultation liaison model improves mental health outcomes versus standard care, but improvement is limited to 3 months after beginning treatment, and applies mainly to patients with depression without suicidal ideation (SOR: B, meta‐analysis of low‐quality RCTs). No outcome differences were noted 12 months or longer after treatment initiation (SOR: B, meta‐analyses of low‐quality RCTs).